ANALISIS KESALAHAN BELAJAR MATEMATIKA SISWA KELAS VIII PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DENGAN METODE ELIMINASI - Martyani, Dita; Maya, Rippi; Zanthy, Luvy Sylviana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
In this study to carry out the learning process, it is necessary to evaluate students to find out errors during the learning process. The purpose of this study was to find out the learning errors of class VIII students in mathematics, the subject of a two-variable linear equation system with the elimination method. This study uses quantitative descriptive research to determine the percentage of students' errors in learning. The subjects of this study used 1 room, namely room 06 class VIII-C with 20 students, consisting of 13 boys and 7 girls. One room has characteristics with low, medium and high categories seen from the acquisition of the Final Semester Assessment. The test instrument of this research used 5 questions. Difficulty in solving mathematics learning problems with two-variable system of linear equations which include: 1). Difficulty in making a mathematical model of the material system of linear equations of two variables; 2). Difficulty in understanding the problem; 3). Difficulty in the calculation process 4). Difficulty in concept.